Pengaruh Pemberian Kuat Arus Listrik Terhadap Tingkat Kelulusan Hidup pada Transportasi Kering Benih Ikan Lele (Clarias sp.) - Rendy Primadona; Susi Lestari; Ace Baehaki (Universitas Sriwijaya, 2017)
The purpose of this research was to know the effect of electric current on the survival rate of Fry finger in dry transportation. This research was conducted at the Aquaculture Laboratory in Aquaculture Study Program of Agriculture Faculty, Sriwijaya University, Indralaya on April and September 2016. The research was conducted using a completely randomized design (CRD) with three treatments and three replications. The stunned fry finger was put in styrofoam and brought for 2 hours. The parameters observed in this study were the number of unconscious fry finger, duration to be conscious, the number of recovered fry finger, and the survival rate. The results showed that stunning with different electric currents had a significant effect on the number of unconscious fry finger of which the largest number was on the current of 0.07A at 96.67%. The fastest duration to be conscious was on 0.05A at 46.67 seconds. The largest number of conscious fry finger at 66.67% was on the current of 0.05A. The best treatment with the survival rate reached 66.67% was obtained by the low current of 0.05A, while the lowest percentage of fry finger viability with the rate 46.67% was reached by the highest current, 0.07A.